Manual removal versus spontaneous delivery of the placenta at caesarean section: a randomized controlled trial by Abdelfattah et al: a letter to the editor - Mahale, Arun Ramkrishnarao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
I highly admire the article “Abdelfattah LE, Bastawy AMA, Fahmy MSED. Manual removal versus spontaneous delivery of the placenta at caesarean section: a randomized controlled trial in International journal of reproduction, contraception, obstetrics and gynecology”.1 Really there is dearth of randomized control trials (RCTs) on this issue of managing third stage of labour during caesarean section, and this is making obstetricians to continue practicing MRP (manual removal of placenta) during caesarean section.2 The general reason for MRP at caesarean section is to save time of surgical procedure of caesarean section. The authors of this article have rightly pointed out by RCT that this does not save time and in fact add many other complications to the outcome of caesarean section surgery.